2008
DOI: 10.1080/00365520701562056
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non-attendance at outpatient endoscopy

Abstract: A longer time on the waiting list and referral by a general practitioner are factors associated with patients failing to keep their endoscopy appointment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 13 publications
7
35
1
Order By: Relevance
“…Using a 20 % baseline non-adherence rate, as reported in previous studies, the model's estimated PPV improves significantly (50 %), with only a modest reduction in the NPV. 7,9,10,15,49 Moreover, the model is equally effective at predicting non-adherence by patients with no prior history of endoscopy, who may be at higher risk of colonoscopy nonadherence. 9 Changes in the model's NPVand PPV have implications for the allocation of resources, like patient navigators, that may improve colonoscopy adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a 20 % baseline non-adherence rate, as reported in previous studies, the model's estimated PPV improves significantly (50 %), with only a modest reduction in the NPV. 7,9,10,15,49 Moreover, the model is equally effective at predicting non-adherence by patients with no prior history of endoscopy, who may be at higher risk of colonoscopy nonadherence. 9 Changes in the model's NPVand PPV have implications for the allocation of resources, like patient navigators, that may improve colonoscopy adherence.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified predictors of non-adherence with colonoscopy scheduling and completion. [9][10][11][13][14][15][16][17] However, no study has described a validated multivariable model for predicting non-adherence with scheduled colonoscopy. Furthermore, no automated method to assess a patient's prior record of nonadherence has been developed, an essential step for any implementation strategy involving large patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are also more likely to no-show when they have to wait longer from the time the appointment is scheduled until the time the procedure occurs (2,4,7). …”
Section: Introductionmentioning
confidence: 99%
“…Two studies claim a better outcome for patients with easier access to gastroscopy in case of gastric cancer [3] and peptic ulcer disease [4]. At the same time Sola-Vera et al [8] showed that patients' tendency to drop an appointment increases with the length of waiting time, which again might have impact on the patient's outcome.…”
Section: Introductionmentioning
confidence: 99%